Effect of Dividend Per Share, Earning Per Share and Price Earning Ratio on Stock Prices PT. Eagle Mahkota Teknologi, Tbk Period 2013-2022 - Fakung Rahman; Tiffani Novia Rachmi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The researchers aim to find out whether there is an effect of Dividend Per Share (DPS), Earning Per Share (EPS), and Price Earning Ratio (PER) on the share price of PT Elang Mahkota Teknologi Tbk (EMTEK) for the period of 2012-2021. This type of research is quantitative descriptive research. The data analysis technique uses the SPSS Version 26 application. From the results of the t-test (partial), the variables DPS, EPS, and PER have a positive effect on stock prices, and the F-test (simultaneous), DPS, EPS, and PER variables significantly impact stock prices. And from the Coefficient of Determination Test (R2) results, the value of R Square in the regression model is 0.708; this means that the contribution of the DPS, EPS, and PER variables together to the stock price is 70.